Retinopathy of prematurity in a controlled trial of prophylactic surfactant treatment. Issue 5 (May 1996) - Pennefather, P M; Tin, W; Clarke, M P; Fritz, S; Strong, N P
Abstract : AIMS: To investigate the incidence of acute and cicatricial retinopathy of prematurity (ROP) in a cohort of premature neonates entered into a randomised, multicentre trial of prophylactic exogenous surfactant for respiratory distress syndrome (RDS) compared with controls receiving surfactant only if severe RDS developed. METHODS: The incidence of acute and cicatricial ROP was assessed in 304 neonates born at less than 30 weeks' gestation in a geographically defined population of approximately three million. RESULTS: There was a trend towards improved survival in the group receiving prophylactic surfactant with 102/151 (67.5%) surviving compared with 82/141 controls (58.2%, p = 0.12). The prophylactic surfactant group would be expected to have an increased risk of ROP due to improved survival, particularly of the most premature infants. However, there was no statistically significant difference in the incidence of acute ROP between the two groups and the incidence of cicatricial ROP was lower in the group receiving prophylactic surfactant (4/100 survivors, 4.0%) compared with neonates receiving rescue surfactant as required (6/81, 7.4%). This difference did not reach statistical significance (p = 0.35). CONCLUSION: The trend for a lower incidence of cicatricial ROP in those neonates treated with prophylactic surfactant compared with the rescue surfactant group, despite improved survival, suggests that the use of prophylactic surfactant also had a beneficial effect on the development of cicatricial ROP.